2008
DOI: 10.1136/gut.2007.142844
|View full text |Cite
|
Sign up to set email alerts
|

Host- rather than virus-related factors reduce health-related quality of life in hepatitis C virus infection

Abstract: Anti-HCV-positive subjects have decreased HRQOL compared to controls. The magnitude of this decrease was clinically important for the SF-36 vitality score. Host and environmental, rather than viral factors, seem to impact on HRQOL level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
2
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 43 publications
4
36
2
3
Order By: Relevance
“…8,10,38 However, in contrast to previous investigations, 10,38 higher ALT concentrations in this study were associated with decreased SF-36 scores in five domains and in two summary components. As CHC has been associated with several extrahepatic manifestations, 3 one may speculate that elevated ALT concentrations might be associated with the activation of a systemic host immune response.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…8,10,38 However, in contrast to previous investigations, 10,38 higher ALT concentrations in this study were associated with decreased SF-36 scores in five domains and in two summary components. As CHC has been associated with several extrahepatic manifestations, 3 one may speculate that elevated ALT concentrations might be associated with the activation of a systemic host immune response.…”
Section: Discussioncontrasting
confidence: 99%
“…Helbling et al showed that low income was the major factor associated with a reduced HRQOL among patients with CHC. 10 In addition, previous investigations have demonstrated the positive influence of education on the HRQOL of patients with this disease. 3,4 Of note, regarding host-related variables, it should be emphasized that the majority of studies assessing the HRQOL of patients affected by CHC have taken place in the context of routine medical care and did not use structured psychiatric interviews to confirm anxiety or mood disorders.…”
Section: Discussionmentioning
confidence: 96%
“…Extrahepatic manifestations of HCV infection may be less important as they are uncommon (although the association between HCV infection and non-Hodgkin lymphoma needs confirmation). The knowledge of one's infection status is a major determinant of altered quality of life because of the increased anxiety caused by the uncertain progression of the disease with its potential consequences (83), and therefore the screening for hepatitis C in 'healthy' subjects has to be undertaken with all due ethical, medical and psychological precautions.…”
Section: Natural History Parameters Morbidity and Mortalitymentioning
confidence: 99%
“…In fact, with sociodemographic variables, such as income, marital status, age or education, co-morbidities had important effects on global QoL of patients living with hepatitis C 19,20 . Because of the close relationship between income and education, it is not easy to discuss specifically the influence of hepatitis C in the association between low income or education level and poor QoL found in this study.…”
Section: Referencesmentioning
confidence: 99%